The Role of the Underground Economy in the Oil Wealth-Growth Nexus: New Insight from Nigeria - Joseph David; Awadh Ahmed Mohammed Gamal; Sultan Ali Mohammed Salem; K. Kuperan Viswanathan; Norasibah Jalil (Organizations and Markets in Emerging Economies)
Research on the relationship between oil wealth and economic growth has shown that the impact of oil can depend on various factors or conditions. However, the role of the underground economy in this relationship remains underexplored. This study aims to fill this gap by examining how the underground economy influences the oil wealth-growth nexus in Nigeria from 1990 to 2022, using the bootstrap autoregressive distributed lag (ARDL) bounds-testing technique. The empirical findings reveal that the effect of oil wealth on economic growth varies with the size of the underground economy. Specifically, the results indicate that the marginal impact of oil wealth on growth is positive when the underground economy is relatively small, but becomes negative as the underground economy expands. This suggests that the underground economy serves as a channel through which oil wealth negatively affects long-term economic growth. The economic implication of this finding is that for sustained long-term growth, increases in oil wealth must be accompanied by significant efforts to reduce the size of the underground economy.